2014
DOI: 10.2741/e693
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs are dysregulated in the cerebral microvasculature of CKD mice

Abstract: Vascular calcification arises during chronic kidney disease (CKD), and increases the risk of cardiovascular mortality. In CKD, alterations of cerebral circulation were linked with an increase in ischemic strokes and behavioral troubles. Studying pathophysiological mechanisms of calcifications and detecting new biomarkers in the cerebral circulation is thus an important issue. microRNAs are small non-coding, single-stranded RNAs that regulate messenger RNAs at the post-transcriptional level. They are involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Dysregulation of miRNAs has been linked to the pathophysiology of many diseases, including kidney and cardiovascular diseases 57 . Our team reported that miR-126 and -223 levels were altered in the aortic wall and serum in murine models of CKD 8 , and in the microcirculation of the brain of CKD mice 9 . Human targets of these miRNAs are shown in Supplementary Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of miRNAs has been linked to the pathophysiology of many diseases, including kidney and cardiovascular diseases 57 . Our team reported that miR-126 and -223 levels were altered in the aortic wall and serum in murine models of CKD 8 , and in the microcirculation of the brain of CKD mice 9 . Human targets of these miRNAs are shown in Supplementary Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The role of miRNAs in chronic kidney disease (CKD) has recently gained increased attention [38,39]. In this study, we found 15 key miRNAs that were significantly enriched in three co-expressed modules.…”
Section: Discussionmentioning
confidence: 82%
“…There is a direct correlation between the accumulation of uremic toxins and their biological and toxic effect in patients [15]. To assess this, we tested the effect of one of the most well-known uremic toxin inorganic phosphate in an in vitro model of vascular calcification: it consisted of human primary cultures of vascular smooth muscle cells (VSMCs) that acquired a pro-calcifying phenotype in presence of pathological levels of inorganic phosphate (Pi) [[16], [17], [18], [19]]. In this model, we found that Pi increased markedly the level of miR-223 [17].…”
Section: Mirnas Are New Players In the Nephrology Fieldmentioning
confidence: 99%
“…Deregulation of cerebral blood flow and protection of the brain have been reported in CKD and are responsible for ischemic strokes and behavioral troubles. We quantified the expression of miR-17 and miR-126 in endothelial cells in cerebral arterioles of WT mice and of pathological models of CKD using RT-qPCR and showed that miR-17 and miR-126 are deregulated and can be used as new biological markers of cerebral troubles of patients in CKD [19].…”
Section: Mirnas Are New Players In the Nephrology Fieldmentioning
confidence: 99%